Wage bargaining and labor market policy with biased expectations - Almut Balleer; Georg Duernecker; Susanne Forstner; Johannes Goensch (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
Recent research documents mounting evidence for sizable and persistent biases in individual labor market expectations. This paper incorporates subjective expectations into a general equilibrium labor market model and analytically studies the implications of biased expectations for wage bargaining, vacancy creation, worker flows and labor market policies. Importantly, we find that the specific assumption about the frequency of wage bargaining crucially shapes the propagation mechanism through which expectation biases affect bargained wages and equilibrium outcomes. Moreover, we show that the presence of biased beliefs can qualitatively alter the equilibrium effects of labor market policies. Lastly, when allowing for biased firms' beliefs, we establish that only the difference between firms' and workers' biases matters for the bargained wage but not the size of biases. – – Jüngste Forschungsergebnisse belegen eine deutliche und persistente Verzerrung individueller Arbeitsmarkterwartungen. In diesem Papier werden subjektive Erwartungen in ein allgemeines Gleichgewichtsmodell des Arbeitsmarktes eingebunden und die Auswirkungen von verzerrten Erwartungen auf Lohnverhandlungen, die Schaffung von Arbeitsplätzen, Arbeitnehmerströme und die Arbeitsmarktpolitik analytisch untersuch. Als besonders wichtig für den Propagationsmechanismus von Arbeitsmarkterwartungen auf Löhne stellt sich die Frequenz von Lohnverhandlungen heraus. Darüber hinaus ist der Unterschied in verzerrten Erwartungen zwischen Unternehmen und Arbeitnehmer wichtiger für den ausgehandelten Lohn als der Umfang der Verzerrungen selbst. Darüber hinaus zeigen wir, dass verzerrte Erwartungen die Gleichgewichtseffekte arbeitsmarktpolitischer Maßnahmen qualitativ verändern kann.
Keywords: E24; J64; D84; 330; Subjective expectations; labor markets; search and matching; bargaining; policy